B7H3 targeting gold nanocage pH-sensitive conjugates for precise and synergistic chemo-photothermal therapy against NSCLC - Bing Chen; Kaifan Zheng; Shubin Fang; Kangping Huang; Chengchao Chu; Junyang Zhuang; Jin Lin; Shaoguang Li; Hong Yao; Ailin Liu; Gang Liu; Jizhen Lin; et al. (Journal of Nanobiotechnology, 2023)
Abstract Background The combination of drug delivery with immune checkpoint targeting has been extensively studied in cancer therapy. However, the clinical benefit for patients from this strategy is still limited. B7 homolog 3 protein (B7-H3), also known as CD276 (B7-H3/CD276), is a promising therapeutic target for anti-cancer treatment. It is widely overexpressed on the surface of malignant cells and tumor vasculature, and its overexpression is associated with poor prognosis. Herein, we report B7H3 targeting doxorubicin (Dox)-conjugated gold nanocages (B7H3/Dox@GNCs) with pH-responsive drug release as a selective, precise, and synergistic chemotherapy-photothermal therapy agent against non-small-cell lung cancer (NSCLC). Results In vitro, B7H3/Dox@GNCs exhibited a responsive release of Dox in the tumor acidic microenvironment. We also demonstrated enhanced intracellular uptake, induced cell cycle arrest, and increased apoptosis in B7H3 overexpressing NSCLC cells. In xenograft tumor models, B7H3/Dox@GNCs exhibited tumor tissue targeting and sustained drug release in response to the acidic environment. Wherein they synchronously destroyed B7H3 positive tumor cells, tumor-associated vasculature, and stromal fibroblasts. Conclusion This study presents a dual-compartment targeted B7H3 multifunctional gold conjugate system that can precisely control Dox exposure in a spatio-temporal manner without evident toxicity and suggests a general strategy for synergistic therapy against NSCLC.